2003
DOI: 10.1002/app.12167
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force and scanning electron microscopic studies of effect of crosslinking system on properties of maleated ethylene–propylene–diene monomer rubber composites filled with short melamine fibers

Abstract: This article reports the development of new composites based on maleated ethylene-propylene-diene monomer (EPDM) rubber and melamine fiber. The compositions are cured using three different types of curing systems: conventional covalent crosslinking based on sulfur and an accelerator, fully ionic crosslinking based on zinc oxide/zinc stearate, and mixed crosslinking involving both covalent and ionic bonds. A dry bonding system comprising resorcinol, hexamethylene tetramine, and hydrated silica, popularly known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…So, the lower Δ G ′/ T v obtained for the pre‐irradiated systems could have been mainly affected by the plasticizing effect of zinc stearate around the interphase between assembled sheets that were used for the rheometer test; this is in agreement with some published cases where the modulus decreased with D −1 …”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…So, the lower Δ G ′/ T v obtained for the pre‐irradiated systems could have been mainly affected by the plasticizing effect of zinc stearate around the interphase between assembled sheets that were used for the rheometer test; this is in agreement with some published cases where the modulus decreased with D −1 …”
Section: Resultssupporting
confidence: 89%
“…The migration of low‐molecular‐weight zinc stearate from the bulk to the surface could be enhanced by electron‐beam irradiation during the pre‐irradiation treatment. Thereby, a thinner layer over the irradiated surface may be formed by zinc stearate moieties; this reduces the mechanical behavior (Scheme ) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanical properties also follow the same order, leading one to believe that surface roughness may be related to the reinforcement of the rubber. On the basis of AFM studies on short melanine fiber-filled rubber composites, Rajeev et al [14,15] have reported that changes in surface roughness of the composites due to aging could be related to changes in hysteresis and mechanical properties of the composites. CONCLUSIONS 1.…”
Section: Resultsmentioning
confidence: 99%
“…The increase of storage modulus (E 0 ) indicates the existence of finest dispersion of short fiber in the rubber matrix and thereby confirms the fiber reinforcement effect. 42,46 The tan δ attains its maximum value within the temperature range of À40 to À42 C Figure 7B. It is attributed to the fact that EPDM exhibits a glass transition temperature within this range, and no peak shift is observed.…”
Section: Dynamic Mechanical Analysismentioning
confidence: 89%